Capital Stock and Productivity: Some Measurement Issues - Hamit-haggar, Mahamat (Université d'Ottawa | University of Ottawa, 2007)
This paper explores whether the effect of different measures of Canadian cap¬ital stock has a direct ineidence on MFP growth in a panel of 39 business sector industries for the period 1987-2004. Using these three alternative measures, we calculate MFP gro